Ultrapurified Alginate Gel Containing Bone Marrow Aspirate Concentrate Enhances Cartilage and Bone Regeneration on Osteochondral Defects in a Rabbit Model. Issue 8 (July 2021) - Xu, Liang; Urita, Atsushi; Onodera, Tomohiro; Hishimura, Ryosuke; Nonoyama, Takayuki; Hamasaki, Masanari; Liang, Dawei; Homan, Kentaro; Gong, Jian Ping; Iwasaki, Norimasa
Background: Ultrapurified alginate (UPAL) gel implantation has been demonstrated as effective in cartilage repair for osteochondral defects; however, cell transplantation within UPAL gels would be required to treat larger defects. Hypothesis: The combination of UPAL gel and bone marrow aspirate concentrate (BMAC) would enhance cartilage repair and subchondral bone repair for large osteochondral defects. Study Design: Controlled laboratory study. Methods: A total of 104 osteochondral defects (1 defect per knee) of 52 rabbits were randomly divided into 4 groups (26 defects per group): defects without any treatment (Defect group), defects treated using UPAL gel alone (UPAL group), defects treated using UPAL gel containing allogenic bone marrow mesenchymal stromal cells (UPAL-MSC group), and defects treated using UPAL gel containing BMAC (UPAL-BMAC group). At 4 and 16 weeks postoperatively, macroscopic and histologic evaluations and measurements of repaired subchondral bone volumes of reparative tissues were performed. Collagen orientation and mechanical properties of the reparative tissue were assessed at 16 weeks. Results: The defects in the UPAL-BMAC group were repaired with hyaline-like cartilage with well-organized collagen structures. The histologic scores at 4 weeks were significantly higher in the UPAL-BMAC group (16.9 ± 2.0) than in the Defect group (4.7 ± 1.9; P < .05), the UPAL group (10.0 ± 3.3; P < .05), and the UPAL-MSC group (12.2 ± 2.9; P < .05). At 16 weeks, the score in the UPAL-BMAC group (24.4 ± 1.7) was significantly higher than those in the Defect group (9.0 ± 3.7; P < .05), the UPAL group (14.2 ± 3.9; P < .05), and the UPAL-MSC group (16.3 ± 3.6; P < .05). At 4 and 16 weeks, the macroscopic evaluations were significantly superior in the UPAL-BMAC group compared with the other groups, and the values of repaired subchondral bone volumes in the UPAL-BMAC group were significantly higher than those in the Defect and UPAL groups. The mechanical properties of the reparative tissues were significantly better in the UPAL-BMAC group than in the other groups. Conclusion: The implantation of UPAL gel containing BMAC-enhanced hyaline-like cartilage repair and subchondral bone repair of osteochondral defects in a rabbit knee model. Clinical Relevance: These data support the potential clinical application of 1-step treatment for large osteochondral defects using biomaterial implantation with cell transplantation.